Rock-Wettability Impact on CO2-Carbonate Rock Interaction and the Attendant Effects on CO2Storage in Carbonate Reservoirs - Al-Yaseri, A. (Elsevier B.V., 2022)
Deep saline aquifers and depleted carbonate reservoirs are generally considered promising locations for subsurface CO2 storage. However, carbonate minerals particularly calcite can react with CO2-saturated brine, resulting in dissolution of carbonate and potentially mechanical compaction. Thus, it is crucial to understand the extent of this reaction in both water-wet and oil-wet scenarios, and subsequently its consequences on CO2 storage in depleted carbonate reservoirs. In this study, medical X-ray computed tomography (CT) was used to image water-wet and oil-wet Indiana limestone core samples before and after CO2 flooding. Changes in the rock matrix and pore structure were further assessed from the porosity and permeability data computed from the CT images. In both cases, imaging shows a significant amount of dissolution resulting in an increase in pore volume after core flooding with live brine and subsequently CO2. This increase in porosity is 46.7 and 19 for the water-wet and oil-wet core, respectively. Likewise, the brine permeability for the water-wet core increased from 9.2 mD (before CO2 flooding) to 108 mD (after CO2 flooding), whereas the permeability for the oil-wet core increased modestly from 9.0 mD to 20.1 mD. These results suggests that the reactivity is less pronounced in the oil-wet rock compared to the water-wet rock. Therefore, the wettability state of a target carbonate reservoir and the subsequent potential for the wettability state to be modified should be considered when assessing the CO2 storage capacity and integrity. Â© 2022